Helvete 1 Incipit (Punctum Books, 2013)
Not to be confused with metal studies, music criticism, ethnography, or sociology, Helvete: A Journal of Black Metal Theory is a speculative and creative endeavor, one which seeks ways of thinking that count as Black Metal events - and indeed, to see how Black Metal might count as thinking. Theory of Black Metal, and Black Metal of theory. Mutual blackening. Therefore, we eschew any approach that treats theory and Metal discretely, preferring to take the left-hand path by insisting on "some kind of connaturality between the two, a shared capacity for nigredo."